2003
DOI: 10.3168/jds.s0022-0302(03)73938-1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Feeding Behavior of Lactating Dairy Cows in Early to Peak Lactation

Abstract: The objectives of this study were to: 1) objectively define meal criteria (minimum interval between meals) of free-stall housed cows fed via a feed alley, 2) determine which measures of feeding behavior were most repeatable, and 3) describe changes in the feeding behavior from early to peak lactation. An electronic monitoring system was used to record individual cow presence (hits; 6-s resolution) at the feed alley for 21 lactating cows for three 8-d periods: period 1, 35 +/- 16 (mean +/- SD), period 2, 57 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
144
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(167 citation statements)
references
References 20 publications
17
144
4
2
Order By: Relevance
“…We noted reductions in feeding behavior overnight compared with morning and afternoon (Figure 4), which agrees with the results of DeVries et al (2003) and Wagner-Storch and Palmer (2003); however, this in contrast to the findings of Nechanitzky et al (2016), who reported a trend for lame cows to have a shorter feeding time at night and lying for over an hour longer than nonlame cows. The cows in the current study were in a larger group (120 vs. 40) and had been subject to less mixing than those in a previous study (Nechanitzky et al, 2016).…”
Section: Barker Et Alsupporting
confidence: 90%
“…We noted reductions in feeding behavior overnight compared with morning and afternoon (Figure 4), which agrees with the results of DeVries et al (2003) and Wagner-Storch and Palmer (2003); however, this in contrast to the findings of Nechanitzky et al (2016), who reported a trend for lame cows to have a shorter feeding time at night and lying for over an hour longer than nonlame cows. The cows in the current study were in a larger group (120 vs. 40) and had been subject to less mixing than those in a previous study (Nechanitzky et al, 2016).…”
Section: Barker Et Alsupporting
confidence: 90%
“…It has been established that young ruminants have a lower molar occlusal contact area; this can reduce jaw movement efficiency to reduce the particle size of food during mastication (Perez-Barberia and Gordon, 1998). Several studies showed that the chewing behavior and more specifically the intake rate were either not affected (Friggens et al, 1998;DeVries et al, 2003) or increased (Abrahamse et al, 2008) by the stage of lactation, which was in contradiction with the results of the present experiment. A study of Pulido and Leaver (2003) showed, by comparing two groups of grazing dairy cows, that the level of milk production could increase the intake rate.…”
Section: --contrasting
confidence: 57%
“…The execution of the computer-vision based system allowed the detection of dairy cow behaviours with a high level of accuracy as proved by the good values of the sensitivity indices (i.e., approximately 92% for the lying behaviour and 86% for feeding and standing ones) which yielded the percentage of cow behaviours correctly classified over the total number of cow bred in the area of the barn under study (Porto et al, 2013(Porto et al, , 2015. Three different behaviours were analysed among those most frequently studied (Overton et al, 2002;DeVries et al, 2003aDeVries et al, , 2003bFregonesi et al, 2007;Provolo and Riva, 2009;Bava et al, 2012) because they are highly related to the comfort of dairy cows: i) feeding, which refers to the standing still position of the cows in the feeding alley with the head through the rack; ii) standing, which refers to the standing still position of the cows in the alley or inside the cubicle or to the deambulation; iii) lying, which refers to all the possible decubitus position of the cows inside the cubicle. The four usual lying positions are the following: long position when the cow lies with the head outstretched forward; short position when the cow lies with the head tilted along one side of the body; narrow position when the cow lies on the sternum with the neck slightly bent, the lower limbs close to the body and the upper limbs that may be outstretched; large position when the cow lies on one side with the lower limbs relaxed.…”
Section: Behaviour Analysis and Heat Stress Indicesmentioning
confidence: 99%